Mapping Obscured Star Formation in the Host Galaxy of FRB 20201124A - Yuxin Dong; Tarraneh Eftekhari; Wen-fai Fong; Adam T. Deller; Alexandra G. Mannings; Sunil Simha; Navin Sridhar; Marc Rafelski; Alexa C. Gordon; Shivani Bhandari; Cherie K. Day; Kasper E. Heintz; et al. (The Astrophysical Journal, 2024)
We present high-resolution 1.5–6 GHz Karl G. Jansky Very Large Array and Hubble Space Telescope (HST) optical and infrared observations of the extremely active repeating fast radio burst (FRB) FRB 20201124A and its barred spiral host galaxy. We constrain the location and morphology of star formation in the host and search for a persistent radio source (PRS) coincident with FRB 20201124A. We resolve the morphology of the radio emission across all frequency bands and measure a star formation rate (SFR) ≈ 8.9 M _⊙ yr ^−1 , approximately ≈2.5–6 times larger than optically inferred SFRs, demonstrating dust-obscured star formation throughout the host. Compared to a sample of all known FRB hosts with radio emission, the host of FRB 20201124A has the most significantly obscured star formation. While HST observations show the FRB to be offset from the bar or spiral arms, the radio emission extends to the FRB location. We propose that the FRB progenitor could have formed in situ (e.g., a magnetar born from a massive star explosion). It is still plausible, although less likely, that the progenitor of FRB 20201124A migrated from the central bar of the host. We further place a limit on the luminosity of a putative PRS at the FRB position of L _6.0GHz ≲ 1.8 ×10 ^27 erg s ^−1 Hz ^−1 , among the deepest PRS luminosity limits to date. However, this limit is still broadly consistent with both magnetar nebulae and hypernebulae models assuming a constant energy injection rate of the magnetar and an age of ≳10 ^5 yr in each model, respectively.